OP75 A qualitative exploration of the intersection between social influence and cultural norms in relation to the development of alcohol consumption practices during adolescence. (September 2018) - MacArthur, GJ; Hickman, M; Campbell, R
Abstract : Background: Despite downward trends in alcohol consumption among young people in the UK, a substantial proportion drink and by the age of 17, at least half of young people report weekly drinking. Evidence regarding effects of school-based interventions to prevent harmful alcohol use is mixed and there remains a need for qualitative research to inform intervention development. We sought to explore young people's perspectives on behavioural and cultural influences relating to alcohol use and the socio-cultural context around alcohol consumption during mid-adolescence. Methods: Forty-two young people (n=21 males, n=21 females) were recruited from schools (n=30, aged 14–15 years) and youth groups (n=12, aged 14–18 years) in the West of England. In schools, participants were randomly selected from year 10 (aged 14–15) with snowball sampling used to maximise diversity of alcohol use, while additional participants were recruited from youth groups via youth workers. Data were collected via semi-structured one-to-one (n=25) and paired (n=4) interviews and one focus group. Interviews were audio-recorded, transcribed verbatim and analysed thematically using NVivo 10. Results: Alcohol use was perceived as a normalised social practice in the wider population and parental influence, attitudes and the provision of alcohol underpinned adolescent attitudes and behaviour. In adolescence, alcohol consumption was associated with being cool, mature and popular, while enabling escape from reality and boosting confidence and enjoyment. Such positive expectancies alongside opportunity contributed to motivating initiation, but social influences were paramount for most, with participants describing a need to fit in or conform with friends to avoid social exclusion or derision. Such influences positioned drinking and intoxication at parties as a normative social practice, further providing opportunities for social learning and incentivising drinking through competition, associations with popularity, and a desire to avoid responsibility for intoxicated friends. Social media weaved into young people's lives the display of positive alcohol-associated depictions of social status, enjoyment and maturity. This intersection of influences, norms and incentives generated a pressurised environment, characterised by conformity being experienced as an obligation to drink, and a sense of unease around abstinence which elicited stigmatising insults. Conclusion: Social influences, cultural norms, incentives and social media contribute to development of a pressurised environment around alcohol consumption during mid-adolescence, driving the escalation of alcohol use as a normative social practice. Our findings highlight the need to acknowledge normative influence and the drivers of cultural norms and practices when developing new interventions to prevent harmful alcohol use during adolescence.